Pemanfaatan Teknologi Networking Komputer sebagai Penunjang Efisiensi Manajemen Pondok Pesantren di Pondok Pesantren Modern Darel Azhar - Muhammad Najhan Tsaani; Nanang Nanang; Dwi Fitria Alfiani; Najwa Masayu Azzahra; Yasin Kamil; Septiano Alvian Ismau; Dede Sandi; Muhamad Lutfi Azizan; Pascal Ismail (Pusat Riset dan Inovasi Nasional, 2026)
The development of information technology requires educational institutions to adapt so that administrative processes and internal management can run more effectively and efficiently. Islamic boarding schools as modern Islamic educational institutions are also not exempt from this need. This Community Service Program (PKM) aims to optimize computer networks and improve the understanding of pesantren staff regarding folder sharing systems, printer sharing, and data management ethics at Pondok Pesantren Modern Darel Azhar, Rangkasbitung, Banten. Implementation methods include initial observation, network design and installation, material delivery and training, data sharing system implementation, and technical evaluation. The results show that the pesantren now has a more organized, stable, and optimally utilized local area network (LAN). In addition, administrative staff gained a better understanding of computer network basics, data sharing systems, and digital data management ethics. This activity has a positive impact on the efficiency of pesantren administrative management and can serve as a model for implementing computer network technology in modern pesantren environments.